Relationship between metabolic reprogramming and drug resistance in breast cancer - Lv, Linlin; Yang, Shilei; Zhu, Yanna; Zhai, Xiaohan; Li, Shuai; Tao, Xufeng; Dong, Deshi (Frontiers in Oncology, 2022)
Breast cancer is the leading cause of cancer death in women. At present, chemotherapy is the main method to treat breast cancer in addition to surgery and radiotherapy, but the process of chemotherapy is often accompanied by the development of drug resistance, which leads to a reduction in drug efficacy. Furthermore, mounting evidence indicates that drug resistance is caused by dysregulated cellular metabolism, and metabolic reprogramming, including enhanced glucose metabolism, fatty acid synthesis and glutamine metabolic rates, is one of the hallmarks of cancer. Changes in metabolism have been considered one of the most important causes of resistance to treatment, and knowledge of the mechanisms involved will help in identifying potential treatment deficiencies. To improve women’s survival outcomes, it is vital to elucidate the relationship between metabolic reprogramming and drug resistance in breast cancer. This review analyzes and investigates the reprogramming of metabolism and resistance to breast cancer therapy, and the results offer promise for novel targeted and cell-based therapies.